Wap lets students ring for results. - Brookmam, Jennie (Times Higher Education Supplement, 2001)
Reports that a pilot version of a Wireless Application Protocol (Wap) software has been developed for German universities. Advantages offered by Wap technology to college students; Prediction that the mobile phone generation of school pupils will soon flood into local universities.